Deep Drawing with Macro Structured for an Environmentally Friendly Process - Alexander BROSIUS; Ali MOUSAVI (Journal of Machine Engineering)
The efficient use of resources are becoming more important due to economic and environmental requirements. In widely used forming processes like deep drawing an avoidance of lubricants – namely dry deep drawing – is a key factor for saving resources. In this paper, a combined approach consisting of a macro-structured tool design and a special modified protective coating is presented. The combination ensures a stable process with a sufficiently wide process window under dry conditions. The absence of lubricants in critical areas has to be compensated by tetrahedral amorphous carbon ta-C films which is additionally structured by Direct Laser Interference Patterning (DLIP) for further improvement of the tribological performance.